Ultrastructure and molecular phylogeny of paraphysomonas vestita (stokes) de saedeller isolated from Laguna de Bay, Philippines - Petronio, Joy Ann G.
A cloned isolate from a freshwater sample of Laguna de Bay was subjected to morphological study by light and electron microscopy, and its small-subunit ribosomal RNA gene was sequenced. Morphological studies showed that the isolate possesses two unequal flagella emerging from the anterior part of the cell. Negative staining revealed the structure of the scales which consist of a baseplate with slightly thickened rim. The narrowing spine arises from the center of the baseplate. These results agree with a previously studies isolate of Paraphysomonas vestita. A phylogenetic analysis based on the sequence information was performed and showed very high similarity (90-99%) to homologous sequences of other Paraphysomonas isolates (and other related Chrysophytes). Both morphological and phylogenetic studies revealed that the isolate is Paraphysomonas vestita. The results of this study agree with previous information on the species of Paraphysomonas.Paraphysomonas vestita is a nanoflagellate protest that plays an important ecological role in freshwater microbial communities as primary producer and as a consumer of prokaryotic and eukaryotic prey. There is little biogeographical information for most of this minute protest despite its significant role in aquatic food webs. In addition, the evolutionary relationships of this organism to other protistan taxa are unclear. These circumstances are largely a consequence ofthe fact that small protists possesses few readily apparent morphological features on which to base taxonomic and phylogenetic schemes and with which to identify them in natural assemblages. No studies on the phylogeny and ultrastructure of a nanoflagellate isolated in the Philippines have been reported so far. Results from this study may serve as a baseline data forfurther phylogenetic and ultrastructural studies on aquatic flagellates.